2012
DOI: 10.1186/1471-2105-13-105
|View full text |Cite
|
Sign up to set email alerts
|

Multiple structure alignment with msTALI

Abstract: BackgroundMultiple structure alignments have received increasing attention in recent years as an alternative to multiple sequence alignments. Although multiple structure alignment algorithms can potentially be applied to a number of problems, they have primarily been used for protein core identification. A method that is capable of solving a variety of problems using structure comparison is still absent. Here we introduce a program msTALI for aligning multiple protein structures. Our algorithm uses several inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…This bb-RMSD indicates a reasonably high level of similarity between the two structures. Further analysis using multiple structure alignment software msTALI [7,8] showed that the conserved core between these three structures (k=6,7 and the x-ray) contained 57 residues. The remaining 19 residues contributed to the divergence in structure (bb-RMSD).…”
Section: B Results Of the Data Mining And Analysismentioning
confidence: 99%
“…This bb-RMSD indicates a reasonably high level of similarity between the two structures. Further analysis using multiple structure alignment software msTALI [7,8] showed that the conserved core between these three structures (k=6,7 and the x-ray) contained 57 residues. The remaining 19 residues contributed to the divergence in structure (bb-RMSD).…”
Section: B Results Of the Data Mining And Analysismentioning
confidence: 99%
“…The phylogenetic analysis feature of msTALI and its significance has been previously reported [17]. It is important to note that the phylogenetic analysis of msTALI is based on all encompassing features of the proteins including sequence, structure, and other biochemical properties [17]. To clarify further, by excluding all the information except the protein sequences, the results of msTALI will converge to that of ClustalW [25].…”
Section: A Using Mstali Phylogenetic Analysis For Subset Validationmentioning
confidence: 91%
“…Prior to investigating the output generated by our multiple structure alignment with msTALI it is important to establish the legitimacy of its alignment [1]. The phylogenetic analysis feature of msTALI and its significance has been previously reported [17]. It is important to note that the phylogenetic analysis of msTALI is based on all encompassing features of the proteins including sequence, structure, and other biochemical properties [17].…”
Section: A Using Mstali Phylogenetic Analysis For Subset Validationmentioning
confidence: 99%
“…Multiple Structure Alignment (MStA) of protein structures can be categorized into four widely different approaches -progressive alignment, core optimization, graph based, and pivot based. Mustang [13], msTali [23] , mulPBA [14], and CE-MC [7] use the progressive alignment approach that creates an alignment of alignments following a guide tree. While this approach does make sense, it suffers from the natural disadvantages of all progressive techniques.…”
Section: Introductionmentioning
confidence: 99%